2017
DOI: 10.1167/iovs.17-21902
|View full text |Cite|
|
Sign up to set email alerts
|

AAV-CRISPR/Cas9–Mediated Depletion of VEGFR2 Blocks Angiogenesis In Vitro

Abstract: PurposePathologic angiogenesis is a component of many diseases, including neovascular age-related macular degeneration, proliferation diabetic retinopathy, as well as tumor growth and metastasis. The purpose of this project was to examine whether the system of adeno-associated viral (AAV)–mediated CRISPR (clustered regularly interspaced short palindromic repeats)–associated endonuclease (Cas)9 can be used to deplete expression of VEGF receptor 2 (VEGFR2) in human vascular endothelial cells in vitro and thus su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 53 publications
0
20
0
1
Order By: Relevance
“…The delivery of the CRISPR/Cas9 components into primary endothelial and other hard-to-transfect cells has been a major obstacle for cardiovascular research. Plasmids, lenti-, adeno-or adeno-associated viral vectors have most often been used to achieve sufficient gene knockout rates in ECs (Abrahimi et al, 2015;Cullere, Plovie, Bennett, MacRae, & Mayadas, 2015;Gong et al, 2017;Miao et al, 2018;Wu et al, 2017). Just recently, we have demonstrated that gene knockouts in human ECs can be established with a crR-NA:tracrRNA:Cas9 RNP approach (Schwefel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of the CRISPR/Cas9 components into primary endothelial and other hard-to-transfect cells has been a major obstacle for cardiovascular research. Plasmids, lenti-, adeno-or adeno-associated viral vectors have most often been used to achieve sufficient gene knockout rates in ECs (Abrahimi et al, 2015;Cullere, Plovie, Bennett, MacRae, & Mayadas, 2015;Gong et al, 2017;Miao et al, 2018;Wu et al, 2017). Just recently, we have demonstrated that gene knockouts in human ECs can be established with a crR-NA:tracrRNA:Cas9 RNP approach (Schwefel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Drugs such as Lampalizumb, Eculizumab, Zimura and Iluvien have initially shown potential effectiveness in clinical trials, and need to be further verified [142][143][144]. As some popular emerging technologies, small interfering RNAs (siRNAs) and clustered regularly interspaced short palindromic repeats (CRISPR)/ CRISPRassociated protein 9 (Cas9) could selectively disrupt the VEGF gene [145][146][147][148][149]. Several inflammatoryrelated cytokines also act on VEGF or VEGF-related mechanisms, so we hypothesized whether can use CRISPR/ Cas9 or siRNAs to target these cytokines and achieved the therapeutic effect on AMD.…”
Section: Potential Applications In Amdmentioning
confidence: 99%
“…No effective treatment for retinal neovascularization (RNV) is available to date. Recent studies have shown that retinal angiogenesis may due to complex interactions among multiple angiogenic stimulators ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%